Dealing with Iron and Other Micro-Irrigation Plugging Problems - Tom Obreza; Ed Hanlon; Mongi Zekri (EDIS)
SL-265, an 8-page illustrated fact sheet by Tom Obreza, Ed Hanlon, and Mongi Zekri, describes problems with emitter plugging and discusses management strategies to overcome and correct causes of plugging in micro-irrigation systems. This publication focuses, in particular, on iron scaling, documenting recent successes in treating this common problem in Florida. Includes sources of further information. Published by the UF Department of Soil and Water Science, August 2008.